2002
DOI: 10.1111/j.1571-9979.2002.tb00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Common Language, Different Meaning: What Meidators Mean When They Talk About Their Work

Abstract: Mediators, for the most part, descrive their work as “facilitation” but what they actually mean varies considerably. Based on an exploratory study with nealy 90 mediators in Canada (all of whom are also mediation trainers), the author describes the great diversity among mediators’understanding of commonly‐used terms like facilitation, transformative, settlement, and humansitic. She also reports on how such factors as context, gender, and number of years mediating affect mediator perceptions of what they do. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…But the confirmation of our hypotheses that female mediators are more oriented to facilitative, relationship‐oriented processes than are male mediators suggests that when they report feeling competent on the job, male and female mediators may mean different things. For men, “competent” may mostly mean “able to reach a stable agreement” or “able to direct a negotiation that leads to an agreement.” For women, it may mean all this but also “able to strengthen the parties” or “able to enhance their relationship.” Cheryl Picard (2002) has shown that male and female mediators use the same word to mean different things. We suggest, for further study, the possibility that male and female mediators mean different things when they speak of competence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the confirmation of our hypotheses that female mediators are more oriented to facilitative, relationship‐oriented processes than are male mediators suggests that when they report feeling competent on the job, male and female mediators may mean different things. For men, “competent” may mostly mean “able to reach a stable agreement” or “able to direct a negotiation that leads to an agreement.” For women, it may mean all this but also “able to strengthen the parties” or “able to enhance their relationship.” Cheryl Picard (2002) has shown that male and female mediators use the same word to mean different things. We suggest, for further study, the possibility that male and female mediators mean different things when they speak of competence.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, female mediators reported being more facilitative in their style, while male mediators testified taking more control over the process toward achieving a settlement (Weingarten and Douvan 1985; Dewhurst and Wall 1994). Cheryl Picard (2002: 256) found that both male and female mediators described their role as “facilitator” but in fact meant different things by it. Women emphasized communication and spoke either of “facilitating communication” or “communication and process,” while men tended to mention only “facilitating process.” One qualitative study of gender and mediation had been previously reported in Israel, but it reached ambiguous conclusions (Desivilya, Ady‐Nagar, and Ben‐Bashat 2004).…”
Section: Instrumental and Transformative Mediationmentioning
confidence: 99%
“…Interestingly, however, mediators are reluctant to define their own approaches as evaluative (Charkoudian et al. ), and express broad differences of interpretation when defining precisely what constitutes a facilitative or evaluative approach to mediation (Picard ).…”
Section: Outcome‐based Studiesmentioning
confidence: 99%
“…Yanick Sarrazin and his colleagues (2005) found that in divorce mediation, facilitative approaches were more effective than directive approaches, although they found little difference in the effectiveness of the two approaches when the divorcing couples no longer had significant emotional involvement with each other. Interestingly, however, mediators are reluctant to define their own approaches as evaluative (Charkoudian et al 2009), and express broad differences of interpretation when defining precisely what constitutes a facilitative or evaluative approach to mediation (Picard 2002).…”
Section: The Role Of Facilitationmentioning
confidence: 99%
“…Picard learns that there is no agreement on the meaning of the words evaluative and facilitative among mediators. 60 Mediators use the words to describe their approach to their practice, yet these words mean different things to different people. 61 Della Noce examines the use of labels in court roster mediator descriptions of mediator activity, concluding that labels of mediator actions such as evaluative, facilitative or transformative do not disclose what it is that mediators actually do.…”
mentioning
confidence: 99%